Gold/Pentablock Terpolymer Hybrid Multifunctional Nanocarriers for Controlled Delivery of Tamoxifen: Effect of Nanostructure on Release Kinetics - Maria-Teodora Popescu; Constantinos Tsitsilianis (Molecules, 2022)
Here, we describe the preparation and characterization of organic/inorganic hybrid polymer multifunctional nanocarriers. Novel nanocomposites of gold nanoparticles using pH-responsive coordination pentablock terpolymers of poly(ε-caprolactone)-b-poly(ethylene oxide)-b-poly(2-vinylpyridine)-b-poly(ethylene oxide)-b-poly(ε-caprolactone), bearing or not bearing partially quaternized vinylpyridine moieties, were studied. The template morphology of the coordination pentablock terpolymer at physiological pH ranges from crew-cut to multicompartmentalized micelles which can be tuned by chemical modification of the central block. Additionally, the presence of 2VP groups allows the coordination of gold ions, which can be reduced in situ to construct gold@polymer nanohybrids. Furthermore, the possibility of tuning the gold distribution in the micelles, through partial quaternization of the central P2VP block, was also investigated. Various morphological gold colloidal nanoparticles such as gold@core-corona nanoparticles and gold@core-gold@corona nanoparticles were synthesized on the corresponding template of the pentablock terpolymer, first by coordination with gold ions, followed by reduction with NaBH4. The pentablock and gold@pentablock nanoparticles could sparingly accommodate a water-soluble drug, Tamoxifen (TAX), in their hydrophobic micellar cores. The nanostructure of the nanocarrier remarkably affects the TAX delivery kinetics. Importantly, the hybrid gold@polymer nanoparticles showed prolonged release profiles for the guest molecule, relative to the corresponding bare amphiphilic pentablock polymeric micelles. These Gold@pentablock terpolymer hybrid nanoparticles could act as a multifunctional theranostic nanoplatform, integrating sustainable pH-controlled drug delivery, diagnostic function and photothermal therapy.